Analisis Peningkatan Performa Proses ETL (Extract, Transform, Dan Loading) Pada Data Warehouse Dengan Menerapkan Delta Extraction Menggunakan Historical Table - Arif Bimo Winnetou; Satrio Agung Wicaksono; Aryo Pinandito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In a certain period of time, most educational institutions produce data with a huge capacity from their operational activities. From those data will appear the need to obtain certain information which is useful as a material of performance evaluation or even as a material of management decision. Data warehouse is one of solutions of these needs. When the capacity and complexity of data warehouse has been increasing, then full extract technique in Extract Transform Loading (ETL) process becomes inadequate, even in others case this technique can not be applied, because this technique causes a large cost. Delta extraction can be one of the solutions of this problem because the process is to extract only the data which has been changing in ETL process. Delta extraction technique will be tested on MySQL DBMS using historical table and trigger. From the result of load test, it can be concluded that trigger gives the load to its parent table, but the waiting time that is required is still tolerable.